Prospective associations between loneliness and emotional intelligence. (7th January 2015) - Wols, A.; Scholte, R.H.J.; Qualter, P.
ABSTRACT: Loneliness has been linked cross‐sectionally to emotional skill deficits (e.g., Zysberg, 2012), but missing from the literature is a longitudinal examination of these relationships. The present study fills that gap by examining the prospective relationships between loneliness and emotional functioning in young adolescents in England. One hundred and ninety‐six adolescents aged 11–13 years (90 females) took part in the study and completed the youth version of the Mayer‐Salovey‐Caruso Emotional Intelligence Test (MSCEIT‐YV) and the peer‐related subscale of the Loneliness and Aloneness Scale for Children and Adolescents (LACA) at two time points, which were 10 months apart. Prospective associations were obtained for male and female adolescents separately using cross‐lagged statistical techniques. Our results showed prospective links between understanding and managing emotions and loneliness for both females and males. Perceiving and using emotions were prospectively linked to loneliness in males only. Possible explanations and directions for future research are discussed.